CASE STUDY INCOME ANALYSIS OF COCONAT PALM SUGAR BUSINESS IN SIMPANG KIRI DISTRICT, SUBULUSSALAM CITY - Yulianita, Siska (Universitas Efarina, 2019)
This study aims to see how much income farmers earn. This research was conducted at the end of November 2018 to February 2019. The data used are primary and secondary data. This research was conducted using direct interview techniques with 23 (twenty three) respondents, in this case the processing of coconut brown sugar and also using written data in the form of documents obtained from the Simpang Kiri District office. This study aims to determine the feasibility of coconut brown sugar business in Simpang Kiri District, Subulussalam City. The data analysis method used in this study is to use the formula for analysis of costs, income and profits. Meanwhile, to calculate business feasibility, the formula used is the Revenue Cost Ratio (R/C), Break Even Point (BEP) and Return On Investment (ROI). The results showed that the average profit received by the coconut brown sugar business craftsmen was Rp. 10,284,428., / per month. Based on the calculation of business feasibility, the R/C is 1.63, the production BEP value is Rp. 1147 kg. BEP price Rp. 8,719, and ROI 63.06%. So it can be concluded that the coconut brown sugar business in Simpang Kiri District, Subulussalam City is feasible to pursue.